Case Series : Orbital Complications In Pediatric Rhinosinusitis - Anna Mailasari Kusuma Dewi; Desy Iriani (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Introduction: Acute bacterial rhinosinusitis in children can cause orbital complications, either directly through fissures or indirectly through veins. Proper treatment can reduce morbidity due to orbital complications. Case: Two cases of orbital complications in pediatric acute bacterial rhinosinusitis caused by adenoid hypertrophy and dental infection. The first case of acute bacterial rhinosinusitis with periorbital cellulitis and left premaxillary abscess accompanied by adenoid hypertrophy and multiple pulp gangrene. The second case of acute bacterial rhinosinusitis with subperiosteal abscess accompanied by adenoid hypertrophy and multiple dental caries. Functional endoscopic sinus surgery (FESS), abscess drainage, adenoidectomy and odontectomy were performed. The culture results of the first patient were Streptococcus anginosus, and it was resistant to tetracycline. Meanwhile, the culture results of the second patient, Staphylococcus epidermidis, were resistant to amoxiclav, ampicillin, cefoxitin, oxacillin, penicillin G, and tetracyclin. Conclusion: Acute rhinosinusitis with orbital complications can caused by adenoid hypertrophy and dental infection. Medical treatment with adequate antibiotic followed by FESS, abscess drainage, adenoidectomy and odontectomy give an optimal result.